Potentiating effect of reovirus on immune checkpoint inhibition in microsatellite stable colorectal cancer - Augustine, Titto; John, Peter; Friedman, Tyler; Jiffry, Jeeshan; Guzik, Hillary; Mannan, Rifat; Gupta, Riya; Delano, Catherine; Mariadason, John M.; Zang, Xingxing; Maitra, Radhashree; Goel, Sanjay (Frontiers in Oncology, 2022)
The majority of colorectal cancers (CRCs) are microsatellite stable (MSS) and resistant to immunotherapy. The current study explores the possibility of oncolytic reovirus to sensitize MSS CRC to immune checkpoint inhibition. While reovirus reduced metabolic activity among KRASMut cells, microarray/computational analysis revealed microsatellite status-oriented activation of immune-response pathways. Reovirus plus anti-PD-1 treatment increased cell death among MSS cells ex vivo. Reduced tumorigenicity and proliferative index, and increased apoptosis were evident among CT26 [MSS, KRASMut], but not in MC38 [microsatellite unstable/MSI, KRASWt] syngeneic mouse models under combinatorial treatment. PD-L1-PD-1 signaling axis were differentially altered among CT26/MC38 models. Combinatorial treatment activated the innate immune system, pattern recognition receptors, and antigen presentation markers. Furthermore, reduction of immunosuppressive macrophages and exhaustion markers, with increased T cell subsets and effector T cell population was observed in MSS tumors. The current investigation sheds light on the immunological mechanisms of the reovirus-anti-PD-1 combination to reduce the growth of MSS CRC.